Periodic Fluctuation of Tidal Volumes Further Improves Variable Ventilation in Experimental Acute Respiratory Distress Syndrome - Güldner, Andreas; Huhle, Robert; Beda, Alessandro; Kiss, Thomas; Bluth, Thomas; Rentzsch, Ines; Kerber, Sarah; Carvalho, Nadja C.; Kasper, Michael; Pelosi, Paolo; de Abreu, Marcelo G. (Frontiers in Physiology, 2018)
Background: In experimental acute respiratory distress syndrome (ARDS), random variation of tidal volumes (VT) during volume controlled ventilation improves gas exchange and respiratory system mechanics (so-called stochastic resonance hypothesis). It is unknown whether those positive effects may be further enhanced by periodic VT fluctuation at distinct frequencies, also known as deterministic frequency resonance. We hypothesized that the positive effects of variable ventilation on lung function may be further amplified by periodic VT fluctuation at specific frequencies. Methods: In anesthetized and mechanically ventilated pigs, severe ARDS was induced by saline lung lavage and injurious VT (double-hit model). Animals were then randomly assigned to 6 h of protective ventilation with one of four VT patterns: 1) random variation of VT (WN); 2) P04, main VT frequency of 0.13 Hz; 3) P10, main VT frequency of 0.05 Hz; 4) VCV, conventional non-variable volume controlled ventilation. In groups with variable VT, the coefficient of variation was identical (30%). We assessed lung mechanics and gas exchange, and determined lung histology and inflammation. Results: Compared to VCV, WN, P04, and P10 resulted in lower respiratory system elastance (63±13cm H2O/L versus 50±14cm H2O/L, 48.4±21cm H2O/L and 45.1±5.9cm H2O/L respectively, P<0.05 all), but only P10 improved PaO2/FIO2 after six hours of ventilation (318±96 vs. 445±110 mm Hg, P<0.05). Cycle-by-cycle analysis of lung mechanics suggested intertidal recruitment/de-recruitment in P10. Lung histologic damage and inflammation did not differ among groups. Conclusions: In this experimental model of severe ARDS, periodic VT fluctuation at a frequency of 0.05 Hz improved oxygenation during variable ventilation, suggesting that deterministic resonance adds further benefit to variable ventilation.